The practice of land pawn in Aceh Besar customary law - Supriadi, Supriadi; Abbas, Syahrizal; Suhaimi, Iman Jauhari, (Opción, 2019)
The aim of the study is to investigate the practice of land Pawn in Aceh Besar Customary Law. This research was juridical and empirical research, with a descriptive-analytical approach. The research results show that land pawn is still practiced in Aceh Besar district, and it is an identity which has been preserved in the customary law. In conclusion, this traditional pawn thrives because of the complicated procedure of taking a loan in official financial institutions, the need for fast money, lender factor, the land without certificate of ownership, the system of loan payment, fear of losing a land and etc.